Causality between economic growth and tourist arrivals : The case of Indo-China - Yong, Wen Yee (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper aims to examine the relationship between tourist arrivals and economic growth in Cambodia, Vietnam, Myanmar, Laos, and Thailand, or more commonly known as the Indo-China countries. Autoregressive Distributed Lag (ARDL) approach which perfonns well with small sample and regardless of the orders of the respective time series is adopted in this study as small sample size is used in this study. The empirical results of this study indicate the existence of short-run causal relationship between tourist arrivals and economic growth in Cambodia, Thailand, and Vietnam.